Technology-Enhanced Learning 2009
DOI: 10.1007/978-1-4020-9827-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Multimedia and Hypermedia

Abstract: Computer-based multimedia and hypermedia resources (e.g., the world wide web) have become one of the primary sources of academic information for a majority of pupils and students. In line with this expansion in the field of education, the scientific study of learning from multimedia and hypermedia has become a very active field of research. In this chapter we provide a short overview with regard to research on learning with multimedia and hypermedia. In two review sections, we describe the educational benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 74 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…In this study, we prioritized ecological validity by conducting the study as an integrated mandatory part of a real higher education engineering course. This is in line with calls for the need for more research in natural learning settings such as classrooms (e.g., Gerjets & Kirschner, ). Prioritizing ecological validity often means that it is not possible to obtain the same level of control that is possible in a lab study.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we prioritized ecological validity by conducting the study as an integrated mandatory part of a real higher education engineering course. This is in line with calls for the need for more research in natural learning settings such as classrooms (e.g., Gerjets & Kirschner, ). Prioritizing ecological validity often means that it is not possible to obtain the same level of control that is possible in a lab study.…”
Section: Discussionsupporting
confidence: 78%
“…Another difference between our study and most previous studies (with the exception of Klingenberg et al, 2020 ) is that this study was conducted as part of a mandatory course rather than a low-stakes lab experiment. In general, it has been argued that conducting more research in natural learning settings will increase the validity of the experimental findings on the topic of IVR learning (e.g., Gerjets & Kirschner, 2009 ). Also, our self-explanation task was a post-intervention task that was applied after a long and cognitively demanding IVR learning simulation, while Parong and Mayer ( 2018 ) used the summarization task after individual segments of the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Chung (2002) and Umagan (2007) explained that in the literature of foreign language listening comprehension; aural listening comprehension is echoed to the term "authentic materials" which according to Hwang (2003) referred to the language which native speakers use to communicate orally. Gerjets and Kirschner (2009) and Shrum and Glisan (2000) showed that empirical listening studies have positive results when listeners used oral authentic texts. Grgurovic and Hegelheimer (2007) found that student who listened to radio tape materials were better in their performance in listening comprehension than those students whose listening instructions did not include radio tapes listening activities.…”
Section: Literature Reviewmentioning
confidence: 99%